To simplify the expression 7x - 3 + 2x + 6, we can combine like terms.
Combining the x terms, we have 7x + 2x = 9x.
Combining the constant terms, we have -3 + 6 = 3.
Therefore, the simplified expression is 9x + 3.
7x-3+2x+6
3 answers
Simplify by using the distributive property.
-3(2x-4
-3(2x-4
To simplify the expression -3(2x - 4) using the distributive property, you need to distribute the -3 to each term inside the parentheses.
-3 * 2x = -6x
-3 * -4 = 12
Therefore, the simplified expression is -6x + 12.
-3 * 2x = -6x
-3 * -4 = 12
Therefore, the simplified expression is -6x + 12.